2010
DOI: 10.1246/cl.2010.902
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Convenient Method to Fabricate Hexagonally Ordered Gold Nanoparticle Arrays Using Diblock Copolymer Micelle Template

Abstract: Monolayer films of hexagonally ordered diblock copolymer micelles were prepared as templates by self-assembly. Gold nanoparticles immediately self-assembled on each individual micelle upon immersion of the template in an aqueous solution of the nanoparticles. This provided a simple, convenient, and inexpensive nanofabrication technique for manufacturing ordered arrays of gold nanoparticles over an extended area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Up to now, numerous studies have focused on the deposition of preformed nanoparticles on block copolymer micellar lms. 41,42,44 For example, Krishnamoorthy et al reported the electrostatic self-assembly of gold nanoparticles onto plasmaetched poly(styrene-block-2-vinylpyridine) (PS-b-P2VP) micellar lm. 44 In that case, both the number of nanoparticles per cluster and the intercluster distance could be tuned conveniently.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, numerous studies have focused on the deposition of preformed nanoparticles on block copolymer micellar lms. 41,42,44 For example, Krishnamoorthy et al reported the electrostatic self-assembly of gold nanoparticles onto plasmaetched poly(styrene-block-2-vinylpyridine) (PS-b-P2VP) micellar lm. 44 In that case, both the number of nanoparticles per cluster and the intercluster distance could be tuned conveniently.…”
Section: Introductionmentioning
confidence: 99%
“…These nanomaterials exhibit size-dependent properties that are very different from those of bulk metals and should lead to novel applications ranging from catalysis and biosensors to optics and data storage. [1][2][3][4][5] Chemical vapor deposition (CVD) 6 and laser ablation 7 are examples of ways that metal nanoparticles can be obtained from bulk metals. Various wet chemical preparations (e.g., polymers, colloids (micelles), and microemulsion) have been demonstrated as facile bottom-up approaches for the reduction of metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…for plasmonic applications. [7][8][9] The colloidal lithography method starts with polymeric particles containing a metal complex as they can be prepared by miniemulsion and emulsion polymerization techniques. 4 Miniemulsion polymerization is a powerful tool for the encapsulation of a variety of different functionalities, including various hydrophobic metal complexes and can be applied for the polymerization of a wide range of monomers.…”
Section: Introductionmentioning
confidence: 99%
“…for plasmonic applications. [7][8][9] The colloidal lithography method starts with polymeric particles containing a metal complex as they can be prepared by miniemulsion and emulsion polymerization techniques. S1 and S9); diameter of the particles at different fabrication states (Tables S2 and S10).…”
Section: Introductionmentioning
confidence: 99%